2016
DOI: 10.1186/s13104-016-2018-2
|View full text |Cite
|
Sign up to set email alerts
|

No considerable changes in papillary thyroid microcarcinoma characteristics over a 30-year time period

Abstract: BackgroundThe prevalence of papillary thyroid microcarcinoma (PTMC) is continuously increasing but its clinical significance and management is still debatable. The aim of this study was to investigate possible changes in the clinical presentation, tumor characteristics, treatment modalities and long-term outcome during the last three decades in patients with PTMC.MethodsWe studied 335 patients with PTMC who were followed up for at least 5 years, from 1982 to 2015, and treated in accordance with the current lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…The American Thyroid Association (ATA) guidelines recommended 5 mm Ø nodules for fine-needle aspiration biopsies (14). Papillary thyroid microcarcinoma changes little in size during a long follow-up (15). Therefore, the study used a 5 mm Ø nodule threshold to predict the aggressiveness of nodules for the prediction of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The American Thyroid Association (ATA) guidelines recommended 5 mm Ø nodules for fine-needle aspiration biopsies (14). Papillary thyroid microcarcinoma changes little in size during a long follow-up (15). Therefore, the study used a 5 mm Ø nodule threshold to predict the aggressiveness of nodules for the prediction of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Vlassopoula et al [27] reported that tumor subtype (papillary or micropapillary) and/or capsular invasion was not effective on the course and outcome of the PTC. Our study showed that incidental diagnosis affects surgical strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Wider access to care and detection of occult tumors have been postulated as predominant influencing factors for this increase, especially in the concurrently unchanged mortality rates for this type of cancer and its favorable course. 2 , 3 - 24 - 26 …”
Section: Discussionmentioning
confidence: 99%
“…A claim of overdiagnosis has also been reported from follow-up and autopsy studies, which state a frequent finding of occult papillary thyroid carcinomas in at least one-third of adults with a variable frequency of 10–36% in thorough autopsy studies. 17 , 26 Those would mostly not produce any harm or progression during adult life. 21 , 27 …”
Section: Discussionmentioning
confidence: 99%